Climate change aggravates non‐target effects of pesticides on dragonflies at macroecological scales. Issue 2 (9th December 2021) - Sirois‐Delisle, Catherine; Kerr, Jeremy T.
Abstract: Critical gaps in understanding how species respond to environmental change limit our capacity to address conservation risks in a timely way. Here, we examine the direct and interactive effects of key global change drivers, including climate change, land use change, and pesticide use, on persistence of 104 odonate species between two time periods (1980–2002 and 2008–2018) within 100 × 100 km quadrats across the USA using phylogenetic mixed models. Non‐target effects of pesticides interacted with higher maximum temperatures to contribute to odonate declines. Closely related species responded similarly to global change drivers, indicating a potential role of inherited traits in species' persistence or decline. Species shifting their range to higher latitudes were more robust to negative impacts of global change drivers generally. Inherited traits related to dispersal abilities and establishment in new places may govern both species' acclimation to global change and their abilities to expand their range limits, respectively. This work is among the first to assess effects of climate change, land use change, and land use intensification together on Odonata, a significant step that improves understanding of multispecies effects of global change on invertebrates, and further identifies conditions contributing to global insect loss.